Mucosal Resident Memory CD4 T Cells in Protection and Immunopathology - Turner, Damian Lanz; Farber, Donna L. (Frontiers in Immunology, 2014)
Tissue resident memory T cells (TRM) are a newly-defined subset that comprises a major component of lymphocyte populations in diverse peripheral tissue sites, including mucosal tissues, barrier surfaces and in other non-lymphoid and lymphoid sites in humans and mice. Many studies have focused on the role of CD8 TRM in protection; however, there is now accumulating evidence that CD4 TRM predominate in tissue sites, and are integral for in situ protective immunity, particularly in mucosal sites. New evidence suggests that mucosal CD4 TRM populations differentiate at tissue sites following the recruitment of effector T cells by local inflammation or infection. The resulting TRM populations are enriched in T cell specificities associated with the inducing pathogen/antigen. This compartmentalization of memory T cells at specific tissue sites may provide an optimal design for future vaccination strategies. In addition, emerging evidence suggests that CD4 TRM may also play a role in immunoregulation and immunopathology, and therefore targeting TRM may be a viable therapeutic approach to treat inflammatory diseases in mucosal sites. This review will summarize our current understanding of CD4 TRM in diverse tissues, with an emphasis on their role in protective immunity and the mechanisms by which these populations are established and maintained in diverse mucosal sites.